Antimicrobial Activity of Nylon Nanocomposites Against Staphylococcus Aureus and Escherichia Coli Bacteria - Omer, Rebaz A.; Gheni, Aqeel I.; Omar, Karzan A.; Ahmed, Lana Omer (Science Journal of University of Zakho, 2019)
This research focuses on the properties and applications of inorganic nanostructured materials and their surface modifications, with good antimicrobial activity. In this research, the synthesized nylon 6, 10 was saturated with different concentrations of aluminum and titanium oxide nanoparticles to form Nano-composites, which used as an antibacterial agent against both harmful Staphylococcus aureus and Escherichia coli bacteria. The nylon Nano-composites become a good antibacterial agent by inhibition bacteria from growing. Staphylococcus aureus was the inhibition zone 6 to 12mm and Escherichia coli from 3 to 11mm. Concentration of Nano-composites become a powerful inhibitor against both gram-positive and gram-negative bacteria.